Pediatric glaucoma: review of recent literature. Issue 2 (March 2017) - Giangiacomo, Annette; Beck, Allen
Abstract : Purpose of review: The purpose of this review is to update the clinician on the recent work in the field of pediatric glaucoma. Recent findings: Using the iCare tonometer to measure intraocular pressure (IOP) in children is highly successful. New data from the Infant Aphakia Treatment Study show that after 5 years of follow-up the risk of developing glaucoma is similar between patients that receive initial intraocular lens implantation and those who are left aphakic. New data show effective lowering of IOP using either approach to trabeculotomy: treating the angle partially with trabeculotomes or circumferentially with a suture or iTrack microcatheter. Recent data on an updated approach to trabeculectomy in children show success in lowering IOP with few complications; however, visual outcomes continue to be suboptimal. A separate study shows that the addition of tenonectomy may not increase surgical success, but may increase survival time and reduce bleb encapsulation. Glaucoma drainage devices in general, and the Ahmed implant in particular, continue to be found to be moderately successful to control IOP, and are therefore employed, especially after initial angle surgery has failed. Summary: Continued work to evaluate the techniques used in the clinical and surgical management of pediatric glaucoma patients supports that both newer and older approaches remain standard of care.